Kelvin probe force microscopy of nanocrystalline TiO2 photoelectrodes - Henning, Alex; Günzburger, Gino; Jöhr, Res; Rosenwaks, Yossi; Bozic-Weber, Biljana; Housecroft, Catherine E.; Constable, Edwin C.; Meyer, Ernst; Glatzel, Thilo (Beilstein Journal of Nanotechnology, 2013)
Dye-sensitized solar cells (DSCs) provide a promising third-generation photovoltaic concept based on the spectral sensitization of a wide-bandgap metal oxide. Although the nanocrystalline TiO2 photoelectrode of a DSC consists of sintered nanoparticles, there are few studies on the nanoscale properties. We focus on the microscopic work function and surface photovoltage (SPV) determination of TiO2 photoelectrodes using Kelvin probe force microscopy in combination with a tunable illumination system. A comparison of the surface potentials for TiO2 photoelectrodes sensitized with two different dyes, i.e., the standard dye N719 and a copper(I) bis(imine) complex, reveals an inverse orientation of the surface dipole. A higher surface potential was determined for an N719 photoelectrode. The surface potential increase due to the surface dipole correlates with a higher DSC performance. Concluding from this, microscopic surface potential variations, attributed to the complex nanostructure of the photoelectrode, influence the DSC performance. For both bare and sensitized TiO2 photoelectrodes, the measurements reveal microscopic inhomogeneities of more than 100 mV in the work function and show recombination time differences at different locations. The bandgap of 3.2 eV, determined by SPV spectroscopy, remained constant throughout the TiO2 layer. The effect of the built-in potential on the DSC performance at the TiO2/SnO2:F interface, investigated on a nanometer scale by KPFM measurements under visible light illumination, has not been resolved so far.
Keywords: atomic force microscopy (AFM); dye-sensitized solar cells (DSC); Kelvin probe force microscopy (KPFM); surface photovoltage (SPV); titanium dioxide (TiO2)